An introduction to language - Fromkin, Victoria (Cengage, 2011)
Ninth Edition, is appropriate for a variety of fields--including education, languages, psychology, anthropology, English, and teaching English as a Second Language (TESL)--at both the undergraduate and graduate levels. This completely updated edition retains the clear descriptions, humor, and seamless pedagogy that have made the text a perennial best-seller, while adding new information and exercises that render each topic fresh, engaging, and current.